‘The Sultan’s self shan’t carry me’: Negotiations of harem fantasies in Byron’s Don Juan - Sarha, Jennifer (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
Lord Byron’s Don Juan is a poem which depends on gendered literary traditions for both its originality and its intelligibility. In the harem episode of cantos V and VI, we can recognise a libertine fantasy, an Orientalist premise, and a picaresque adventure, but also some traces of epic, the gothic and literature of sensibility. Yet, these tropes are consistently complicated in the poem and used to undermine the gendered foundations of their traditions. This essay considers the formulation of such subversions through explicitly literary paradigms: what signs of gender are referred to, and how are they made intelligible as fictional constructs? By interrogating the use of gendered tropes, their formation as intelligible concepts within literary history, and their negotiations with sexualised conventions of narrative, I intend to highlight the discrepancies in the heteronormative construction of these literary paradigms and Byron’s use of them to suggest sexual fluidity.